(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the Researchers conducting this research is to calculate and formulate the costs incurred in the distribution of goods delivery activities in logistics service company in the city of Bandung, so that the calculations and formulations can display more real transportation costs. This study uses descriptive analysis which is used to calculate a data with this analysis the researchers found an accurate calculation that shows that transportation costs there are various types of costs from fixed costs, variable costs, to investment costs, carried out using data collection techniques including observation, and interviews. From the research that has been done shows the costs that make up the company’s transportation costs can be classified as fixed costs, variable costs, and investment costs. And it was found that transportation costs can be calculated more accurately.